Tractates Gittin and Nazir - Guggenheimer, Heinrich W. (Studia Judaica, 2007)
The ninth volume of this edition, translation, and commentary of the Jerusalem Talmud contains two Tractates. The first Tractate, "Documents", treats divorce law and principles of agency when written documents are required. Collateral topics are the rules for documents of manumission, those for sealed documents whose contents may be hidden from witnesses, the rules by which the divorced wife can collect the moneys due her, the requirement that both divorcer and divorcee be of sound mind, and the rules of conditional divorce. The second Tractate, "Nazirites", describes the Nasirean vow and is the main rabbinic source about the impurity of the dead. As in all volumes of this edition, a (Sephardic rabbinic) vocalized text is presented, with parallel texts used as source of variant readings. A new translation is accompanied by an extensive commentary explaining the rabbinic background of all statements and noting Talmudic and related parallels. Attention is drawn to the extensive Babylonization of the Giṭṭin text compared to genizah texts.